Greenfield, mergers & acquisitions, energy consumption, and environmental performance in selected SAARC and Asean Countries - Abu Bakar, Nor'Aznin; Raji, Jimoh Olajide; Adeel-Farooq, Rana Muhammad (EconJournals, 2019)
This study by using the random effects (RE) and robust least square estimates (RLS) examines the influence of two different types of FDI namely Greenfield (GF), Mergers & Acquisition (M&A) and energy consumption, on environmental performance of the eight selected economies in SAARC and ASEAN regions over the 2003-2014 period. Moreover, economic growth and population growth are used as controlled variables. The originality of this study is the use of Environmental Performance Index (EPI) to examine the effects of two different types of foreign capital inflows on the environment. According to the empirical outcomes of this study, GF and M&A investments have exacerbated the environmental performance in the selected eight SAARC and ASEAN countries, hence confirm the Pollution Haven Hypothesis (PHH) to be valid. In addition, energy consumption and population growth are also found to be serious havoc for the environmental performance in this case. Nonetheless, economic growth has improved the overall environmental performance in these countries. The study suggests the formulation and enforcement of strict environmental regulations to seek environment friendly and energy efficient GF and M&A investments. In addition, renewable energy use and population control policies are highly desirable in these countries for clean and healthy environment. Accordingly, these economies are recommended to develop policies to realize sustainable economic development for improved environmental performance.